PEMBELAJARAN TEKNIK MIND MAP BERBASIS KEARIFAN LOKAL DI MASA NEW NORMAL SISWA SEKOLAH DASAR MERAUKE - Rudolfus Ruma Bay; Yonarlianto Tembang; Lay Riwu (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
Online learning is the best solution during a pandemic like this because it is a place to transmit knowledge. However, not all feel that it is all good because of the limitations of communication tools that must use the internet as one of the requirements for learning so that steps are taken so that learning is carried out face-to-face. The purpose of this study was to improve student learning outcomes in the affective and cognitive domains using a mind map technique based on local wisdom. This research is a cyclical classroom action research. The subjects of this study were students of class IVb SD Inpres Kampung Baru Merauke, totaling 22 students in the 2021/2022 academic year. The data of this study were obtained through observation and tests. The results showed that there was an increase in student learning outcomes in the affective domain at each meeting in the cycle according to the aspects, namely; 1) curiosity; 2) cooperation; 3) communication skills; 4) thorough; 5) be careful; and 6) persistence. Likewise, student learning outcomes in the cognitive domain obtained during the learning process also experienced an increase in the percentage, namely in the first cycle students who completed 13 students completed or 59.09%, in cycle 2 students experienced an increase in classical learning outcomes by 86.36% students completed 18 students. Thus, these results indicate that the use of local wisdom-based mind map techniques can improve student learning outcomes.